HUBUNGAN ANTARA CITRA KULINER DAN KEPUASAN WISATAWAN TERHADAP LOYALITAS DESTINASI PULAU BANGKA - Jimmy Muller Hasoloan Situmorang; Felicia Angelina; Nonot Yuliantoro (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2021)
Bangka Island is one of the largest tin-producing islands in Indonesia which recently has started to develop its tourism sector. Bangka Island is famous as one of the culinary centers, particulary in seafood products, from a variety of fresh seafood to processed products, such as kemplang, crackers, lakso, koba noodles, and many others. The aim of the study was to identify whether culinary image in Bangka Island affects tourist satisfaction and destination loyalty as well as to recognize whether tourist satisfaction affects destination loyalty. The result of this study indicated that from four culinary image dimensions on Bangka Island; food quality, contextual features, food culture, and atmosphere, only food quality and contextual features that had significant positive effect on tourist satisfaction and destination loyalty, whilst food culture and atmosphere had no significant effect. More result showed that tourist satisfaction had a positive influence on destination loyalty. Improvements are needed to enrich the culinary image of Bangka Island to facilitate the development of its tourism. Both local government and salers need to find a solution to increase tourist perceptions and to make Bangka Island a good destination place. This research was made based on quantitative research with questionnaire data collection method. The sampling technique in this research was nonprobability sampling technique that used accidental sampling method with the provision that the respondents were Indonesian tourists who have visited and tried local food of Bangka Island. The quantitative data then processed using simple regression analysis statistical method and multiple regression analysis.